Loss of IGF2 imprinting is associated with abrogation of long-range intrachromosomal interactions in human cancer cells - Vu, Thanh H. (Oxford University Press, 2010)
Nuclear architecture and chromatin geography are important factors in the regulation of gene expression, as these components may play a vital epigenetic role both in normal physiology as well as in the initiation and progression of malignancies. Using a modification of the chromosome conformation capture (3C) technique, we examined long-range chromatin interactions of the imprinted human IGF2 gene. We demonstrate that numerous intrachromosomal interactions occur along both parental alleles in normal tissues, where the IGF2 is paternally expressed, as well as in normal liver where gene expression is biallelic. Long-range and allele-specific interactions occur between the IGF2/H19 imprinting control region-1 (ICR1) and ICR2, a region which regulates an imprinted gene cluster nearly a megabase distant from IGF2. Loss of genomic imprinting is a common epigenetic event in cancer, and long-range interactions have not been examined in malignant cells. In cancer cell lines in which IGF2 imprinting is maintained (MOI), essentially all of the 3C interactions seen in normal cells were preserved. However, in cells in which IGF2 imprinting was lost (LOI), nearly all of the long-range chromatin interactions involving IGF2 were abrogated. A three-dimensional computer model depicts the physical interactions between the IGF2 promoter and ICR1 in MOI cells, while the model of LOI lung cancer cells is flattened with few long-range interactions. This dramatic change in the three-dimension configuration of the chromatin at the IGF2 locus in LOI cancer cells suggests that the loss of imprinting may lead to a variety of changes in gene expression in addition to changes in IGF2 transcription.